2018
DOI: 10.3390/su10124843
|View full text |Cite
|
Sign up to set email alerts
|

Imposed Water Deficit after Anthesis for the Improvement of Macronutrients, Quality, Phytochemicals, and Antioxidants in Rice Grain

Abstract: The control of protein and amylose content is the principal challenge in rice nutrient and quality improvement. In this study, water deficits in 2- and 3-day intervals were imposed on two Japonica cultivars K1 and K3, and an Indica K4 subtype after anthesis to harvest. It was observed that although rice yield was affected, the protein content was increased 6.53–6.63% to 9.93–10.16%. The amylose quantity was reduced significantly from 22.00–22.43% to 16.33–17.56%, while fatty acids in rice grain were not influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
4
11
1
Order By: Relevance
“…The 10-day interval water stress condition after transplanting affected to increase anthocyanin both in drought tolerant and sensitive varieties (Khan et al, 2017). A similar response was reported by Rayee et al (2018) reporting that anthocyanin in japonica and indica rice varieties greatly enhanced by the 3-day interval of water deficit after anthesis to harvest. However, the response of anthocyanin concentration to water condition is variable, depending on several key factors such as the degree of water restriction and microclimates (Esteban et al, 2001;He et al, 2010).…”
Section: Zn Fe Yieldsupporting
confidence: 81%
“…The 10-day interval water stress condition after transplanting affected to increase anthocyanin both in drought tolerant and sensitive varieties (Khan et al, 2017). A similar response was reported by Rayee et al (2018) reporting that anthocyanin in japonica and indica rice varieties greatly enhanced by the 3-day interval of water deficit after anthesis to harvest. However, the response of anthocyanin concentration to water condition is variable, depending on several key factors such as the degree of water restriction and microclimates (Esteban et al, 2001;He et al, 2010).…”
Section: Zn Fe Yieldsupporting
confidence: 81%
“…The results were in agreement with a previous report by Oh et al, which showed that the drought stress induced by withholding water for 4 days improved the TPC and TAC in lettuce [15]. Furthermore, numerous studies have shown that drought stress enhances one or both enzymatic and nonenzymatic antioxidants in a wide range of plants [31][32][33][34][35]. Moderate drought stress can improve plant drought tolerance, and enhance the antioxidant system [30,36].…”
Section: Bioactive Compounds Antioxidant Activity and Plant Growthsupporting
confidence: 92%
“…Total phenolic content (TFC) were strongly accelerated in both rice cultivars (Table 2). In this study, the TFC in rice leaves and roots under chilling stress was higher as compared to the TFC in a previous study under water deficit stress [26]. The TFC included both free and bound form in leaves and roots was associated with the reduced temperature ( Table 2).…”
Section: Discussioncontrasting
confidence: 41%